Electrochemical Microscopy Based on Spatial Light Modulators: A Projection System to Spatially Address Electrochemical Reactions at Semiconductors. Issue 4 (1st January 2018) - Vogel, Yan B.; Gonçales, Vinicius R.; Gooding, J. Justin; Ciampi, Simone
Abstract : Here we describe a "light projector" system that can address, i.e. "read and write" electrochemical reactions on a non-structured macroscopic semiconducting electrode with spatial and temporal resolution. In our approach the illumination of an amorphous silicon electrode/electrolyte interface is spatially defined by means of a ferroelectric micromirror system that gives total freedom on both the two-dimensional light profile (illumination shapes) as well as on the transient times of the projected images. The device has no moving parts and allows for spatial and temporal control of the illumination stimulus driving local changes to the rate of an electrochemical reaction. The performance of the system is assessed by generating microscale patterns of Cu2 O on the electrode ("electrochemical writing") followed by their 2D current mapping ("electrochemical reading") using methanol electro-oxidation and carbon dioxide electro-reduction. The latter illustrate the electrochemical imaging aspects of the device using two technologically relevant examples.